Beginning database design solutions - Stephens, Rod 1961- (Wiley Pub., 2009)
This book is intended for IT professionals and students who want to learn how to design, analyze, and understand databases. The material will benefit those who want a better high-level understanding of databases such as proposal managers, architects, project managers, and even customers. The material will also benefit those who will actually design, build, and work with databases such as database designers, database administrators, and programmers. In many projects, these roles overlap so the same person may be responsible for working on the proposal, managing part of the project, and designin.
"Wrox programmer to programmer"--Cover. - Includes index. - Print version record
Keywords: Database design; Databases; Bases de données; Conception; COMPUTERS; Desktop Applications; Databases; COMPUTERS; Database Management; General; COMPUTERS; System Administration; Storage & Retrieval